MicroRNA396-mediated alteration in plant development and salinity stress response in creeping bentgrass. Issue 1 (1st May 2019) - Yuan, Shuangrong; Zhao, Junming; Li, Zhigang; Hu, Qian; Yuan, Ning; Zhou, Man; Xia, Xiaoxia; Noorai, Rooksie; Saski, Christopher; Li, Shigui; Luo, Hong
Abstract: The conserved microRNA396 (miR396) is involved in plant growth, development, and abiotic stress response in multiple plant species through regulating its targets, Growth Regulating Factor ( GRF ) transcription factor genes. However, the role of miR396 has not yet been characterized in perennial monocot species. In addition, the molecular mechanism of miR396-mediated abiotic stress response remains unclear. To elucidate the role of miR396 in perennial monocot species, we generated transgenic creeping bentgrass ( Agrostis stolonifera ) overexpressing Osa-miR396c, a rice miRNA396 gene. Transgenic plants exhibited altered development, including less shoot and root biomass, shorter internodes, smaller leaf area, fewer leaf veins, and epidermis cells per unit area than those of WT controls. In addition, transgenics showed enhanced salt tolerance associated with improved water retention, increased chlorophyll content, cell membrane integrity, and Na + exclusion during high salinity exposure. Four potential targets of miR396 were identified in creeping bentgrass and up-regulated in response to salt stress. RNA-seq analysis indicates that miR396-mediated salt stress tolerance requires the coordination of stress-related functional proteins (antioxidant enzymes and Na + /H + antiporter) and regulatory proteins (transcription factors and protein kinases). This study establishes a miR396-associated molecular pathway to connect the upstream regulatory and downstream functional elements, and provides insight into the miRNA-mediated regulatory networks. Salt tolerance: How plants handle high (salt) stress situations: A small molecule, miR396, plays a big role in how plants respond to salt stress, a growing constraint on global crop yield. Salt stress prevents plants from absorbing nutrients, causes oxidative stress, and destroys key cellular machinery; some plants cope better than others. Hong Luo at Clemson University in South Carolina, USA and coworkers investigated how creeping bentgrass handles high salinity, focusing on the microRNA miR396, previously implicated in salt tolerance. Artificially elevating miR396 improved bentgrass' salt tolerance. Further investigation showed that miR396 triggered increases in proteins that pump excess salt out of cells, others that prevent water loss, and antioxidant production. miR396 was found to be a master regulator that orchestrates many lines of defense against excess salt. Understanding how these pathways are activated and integrated could help in breeding more salt-tolerant crops.